(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2022)
This paper inquiries the performative turn in the theater of Monica Calle – Casa Conveniente, where the speech, apparently excluded, and the dramaturgy of the body, in exacerbation, will become a mode of "absent text". To this end, two performances are compared, Ensaio para uma Cartografia and O Escuro que te Ilumina ou as Últimas Sete Palavras de Cristo, together with its creative universes. Developing a historiography of the company, discussing a spectatorship of the aesthetics of this theatre-maker and textualizing the experiences of the body, we come to suggest that a performative cartography is the result of the spatial and subjective maps of these universes. Based on an autoethnographic approach, we have immersed (in a theoretical and practical way) in the drive, the desire, the physical and spiritual endurance and in the singular-collective dialectic – features of Calle’s artistic work. Using distinct writing regimes, the paper is divided into two parts: in I, the creation phases of the two universes are analyzed and, in II, a committed essay as a researcher-performer is sketched.